Application of Discussion Method to Improve Learning Outcomes of Islamic Religious Education in Class V - Betry Yeti (BiCED Proceeding, 2024)
The study aims to determine the impact of using the discussion method on students' interest and learning outcomes in Islamic Religious Education in grade V of SD Negeri 06 Batang Timblan. The research was conducted in two cycles, each involving observation of student activities and assessment of test results. The findings show that in cycle I, many students were not active and did not achieve the Minimum Completion Criteria (KKM). In cycle II, improvements made in the discussion method successfully increased student participation, with 75% of students reaching KKM. However, 25% of students still did not achieve KKM. This study concludes that the discussion method can enhance students' learning interest and outcomes, but further efforts are needed to ensure that all students reach the KKM.